Disability in higher middle schools: The specialist assistance as integrative function - Paniccia, Rosa Maria; Giovagnoli, Fiammetta; Di Ruzza, Federica; Giuliano, Sonia (Quaderni di Psicologia Clinica, 2014)
This paper deals with the report of a training intervention addressed to Specialist Assistants (SA) who care for students with disabilities in higher middle schools in Rome. The aim of the intervention was to develop SAs’ organizational competence, that is the competence to analyze their work context - including school, families, services - and emotional dynamics characterizing it, without relying on collusive actions but by pursuing an integration-oriented project.